Regard the Past - Shellabarger, Samuel (Tufts Archival Research Center, 2006)
In a recording aired posthumously, Samuel Shellabarger describes his beliefs in his dependence upon God for eternal life, in the existence of natural laws that govern values and morality, and in the value of using the past to inform future decisions.